The impact of early surgical intervention in free intestinal perforation: a time-to-intervention pilot study. Issue 1 (December 2015) - Hecker, Andreas; Schneck, E.; Röhrig, R.; Roller, F.; Hecker, B.; Holler, J.; Koch, C.; Hecker, M.; Reichert, M.; Lichtenstern, C.; Krombach, G.; Padberg, W.; et al.
Abstract Purposes An abdominal inflammatory focus is the second most often source of sepsis with a high risk of death in surgical intensive care units. By establishing evidence-based bundled strategies the surviving sepsis campaign provided an optimized rapid and continuous treatment of these emergency patients. Hereby the hospital mortality decreased from 35 to 30 %. Sepsis treatment is based on three major therapeutic elements: surgical treatment (source control), antiinfective treatment, and supportive care. The international guidelines of the surviving sepsis campaign were updated recently and recommend rapid diagnosis of the infection and source control within the first 12 h after the diagnosis (grade 1c). Interestingly this recommendation is mainly based on studies on soft tissue infections. Methods In this retrospective analysis 76 septic patients with an intraabdominal inflammatory focus were included. All patients underwent surgery at different time-points after diagnosis. Results With 80 % patients of the early intervention group had an improved overall survival (vs. 73 % in the late intervention group). Conclusions Literature on the time dependency of early source control is rare and in part contradicting. Results of this pilot study reveal that immediate surgical intervention might be of advantage for septic emergency patients. Further multi-center approaches will be necessary to evaluate, whether the TTI has any impact on the outcome of septic patients with intestinal perforation.